1997
DOI: 10.1002/clc.4960200217
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced external counterpulsation as an adjunct to revascularization in unstable angina

Abstract: Summary:Enhanced external counterpulsation (EECP) is an effective noninvasive treatment for chronic stable angina. Despite intensive risk factor modification, a patient required two surgical coronary revascularizations and seven multivessel angioplasties over a 26-month period, demonstrating recunent unstable angina and persistent thallium perfusion defects despite revascularization. Post EECP, angina was relieved, thallium defects were resolved, and the patient has remained asymptomatic for 36 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1998
1998
2004
2004

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Pre-and posttreatment thallium scans and ETT provide objective evidence that EECP [14][15][16][17][18][19][20][21][22][23][24][25] is associated with resolution of reversible ischemia in many cases. Tissue pathology in animal studies [18][19][20][21] suggest collateral revascularization in the coronary arteries as one physiologic mechanism in which EECP leads to lasting subjective and objective improvement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-and posttreatment thallium scans and ETT provide objective evidence that EECP [14][15][16][17][18][19][20][21][22][23][24][25] is associated with resolution of reversible ischemia in many cases. Tissue pathology in animal studies [18][19][20][21] suggest collateral revascularization in the coronary arteries as one physiologic mechanism in which EECP leads to lasting subjective and objective improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue pathology in animal studies [18][19][20][21] suggest collateral revascularization in the coronary arteries as one physiologic mechanism in which EECP leads to lasting subjective and objective improvement. Patients who have had coronary artery bypass graft surgery before EECP are more likely to have improvement of ischemia; [14][15][16] researchers have suggested that the larger, patent grafts may increase diastolic aortic retrograde flow and enhance revascularization. Peripheral vascular effects may be another physiologic mechanism, as demonstrated by lower double product on ETT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation